Meningkatkan Keterampilan Literasi Peta Menggunakan Game Based Learning Model Pada Siswa Sekolah Menengah Pertama - Linna Mahpuzah; Junaidin Junaidin; Arif Arif (Jurnal Ilmiah Profesi Pendidikan, 2025)
Low literacy skills among junior high school students are a problem in geography learning, especially in relation to understanding symbols, scales, and orientation. This study aims to determine the effectiveness of using the Seterra educational game based on Game-Based Learning in improving the map literacy of seventh-grade students at SMP Plus Miftahul Falah. The method used was Classroom Action Research (CAR) based on the Kemmis & Taggart model with three cycles, consisting of planning, action, observation, and reflection. Data were obtained through map literacy tests and observation of learning activities. The results showed an increase in the average student score from 45 on the pretest to 60 in cycle I, 75 in cycle II, 82 in cycle III, and 87 on the posttest. Seterra-based learning also increased student motivation and activity during the learning process. Thus, Seterra proved to be effective as an interactive medium for improving map literacy and is recommended as an alternative to technology-based geography learning.